Kendala Teknologi, Pendanaan dan Ketersediaan Bahan Baku Biomassa dalam Pengembangan Energi Terbarukan - Arsyad Arsyad; Syaifuddin Yana; Radhiana Radhiana; Ulfia Ulfia; Fitriliana Fitriliana; Juwita Juwita (Fakultas Teknik, 2023)
AbstractThe world’s energy needs keep rising but numerous difficulties remain to meet energy needs. Technological, financing, and biomass raw material issues hinder biomass energy expansion. Renewable energy development faces this main challenge. Converting biomass into energy is still expensive. Hightech investments cost more. Modern technology demands lots of raw materials. Industrial biodiesel capacity is 12.5 million kilolitres. 3 million kilolitres, or 25%, are used. Funding issues also exist. Bioenergy processors require incentives to invest. Improve regulations to sustain investment. The financial services authority should sponsor and finance green projects like renewable energy development to help this industry grow and survive. However, feedstock availability and sustainability remain the biggest challenge. Feedstock supply and biomass price stability remain challenges. Therefore, stakeholders and the government and businesses that use their resources must cooperate and coordinate. Planning, regulation, and coordination are the keys to preserving the biomass resource activity cycle. The government should strengthen regulations through linked ministries to ensure its sustainability.Keywords: biomass energy conversion, technological limitations, finance limits, biomass raw material availability, legislation for biomass energy